A Review on Panic Disorder with Associated Comorbidites and Its Miasmatic Correlation With Homoeopathy (Advancements in Homeopathic Research, 2024)
Panic disorder is a complex condition that requires  a multifaceted treatment approach. Panic disorder  tends to be a chronic condition which runs an  unremitting course and leads to social, occupational  along with physical disability. The disorder is often  associated with intense uncontrollable fear or anxiety  mainly due to anticipation of threatening event.  They have significant impact on the quality of life  of the patient. Homoeopathy works holistically  treating the patient through individualization and by  taking into account mental symptoms including will,  intellect, memory, emotion and physical as well as  particulars. Homoeopathy cures miasmatically if any  of which is persisting in the patient, reduces the use  of conventional treatment and serves as a boon in  patients suffering from panic disorder.
Keywords: Panic disorder; Homoeopathy; Miasm; DSM-5 Criteria; Chronic disease; smilimum